Reconnecting with the Public: Communication Strategies to Address the Hypertension Crisis in Banjarmasin - Ritonga, Adam George (LSPR Institute of Communication & Business, 2022)
This article presents a comprehensive communication strategy to tackle the hypertension crisis in Banjarmasin, Indonesia, where the prevalence of hypertension remains significantly high despite ongoing government interventions. The Ministry of Health (KEMENKES), in coordination with local healthcare institutions like PUSKESMAS, has launched a targeted campaign aimed at increasing public awareness, improving prevention measures, and rebuilding trust in the government's commitment to healthcare. The campaign integrates multiple communication channels, including media outreach, public seminars, and strategic partnerships with influencers and local businesses that promote healthy lifestyle choices. A key component of the strategy is the appointment of Regional Ambassadors who will oversee community engagement and lead health education efforts across Indonesia. Social media platforms will also play a central role in disseminating key messages about hypertension prevention, delivered through influencers, volunteers, and interactive online content. Additionally, the campaign incorporates community-driven activities, such as